Cellular impact of hypovolemia: anestesiología - Peri, Homero (Cirugía del Uruguay, 1973)
The paper follows the general orientation of anesthesiology, towards the preservation and recovery of organic functions through generic attention to the cells and their means of support. Metabolic cellular consequences of anoxia due to hipovolemia are discussed; metabolic acidosis is considered a symptom or consequence, and not a cause. Stress is Jaid on the considerable size and relative functional autonomy of the capillary and microcirculation. Importance is attributed to the functional extracellular liquid due to its volume, its tempering function and its marked reduction in the presence of hipovolemia, while pointing out the importance of restoring it and to the value of diuresis in the light of a change in the hypothesis of organic response in the face of a disease requiring surgery, of trauma and of anesthesia.